Narrativa transmedia para desarrollar habilidades socioemocionales de los alumnos de educación básica en la asignatura de lengua y literatura. - Pagalo Paca, Gloria Piedad (2025)
This thesis investigates "Socioemotional Skills through Transmedia Strategy in the Subject of Language and Literature at the Support Center 'Time for Us'." The study focuses on the application and effectiveness of a transmedia strategy to enhance socioemotional skills and literary understanding among basic education students. The main objective is to develop a transmedia educational program in Language and Literature centered on "The Search for True Heroism," to foster empathy and effective interaction among 8th-grade basic education students. The methodology adopted is quasi-experimental, utilizing both quantitative and qualitative analyses to assess changes in socioemotional skills and academic performance of students before and after the transmedia intervention. Techniques include questionnaires, direct observations, and semi-structured interviews. Results indicate that Transmedia Narratives significantly improve literary comprehension and socioemotional skills, such as empathy and conflict resolution. The conclusion of the study confirms that using transmedia narratives in an educational setting is an effective strategy to engage students' attention and enhance their emotional and academic development.